Students’ Activities in Learning About Human Organ of Motions and Environment with Scientifis Approach in the Application of 2013 Curriculum - Prabawati, Ratna Juwita Dian; Wardani, Sri; Utomo, Cahyo Budi (Educational Management, 2021)
This study is purposed to describe the student’s activities and the obstacles during the learning process of 5thgrade’s Theme 1 Organ of Motions of Animals and Human, Sub-theme 2 Organ of Motions in Human and the Environment. This study was conducted with qualitative method by using case study strategy. The subject of this study is the 5 grader students in Dabin-I UPK Banyumas. The data was collected by doing observation, interview and documentation. The collected data was analized by doing data reduction, data display, conclusion and verification. The validity test was conducted by doing credibility test using technique and source triangulation. The result of this study showed that the student’s activities have been corresponding the scientific syntaxes, which included observation, asking question, trying, reasoning, and communicating, although it’s not optimaly done in the classroom. Students can conduct the learning process with teacher’s gaudance. The teacher used the autenthic valuation to evaluate the student’s competence, although it wasn’t done in every learning season. Teachers have done the valuation including the attitude, knowledge, and skill evaluation. The obstacles can be found in learning planning, practice , and evaluation.